PENGARUH PENGELOLAAN SARANA DAN PRASARANA TERHADAP KINERJA PERSONIL POLRI PADA KANTOR SATLANTAS POLRES TEBO - Hamsyah Hamsyah; Osrita Hapsara; Sakinah Sakinah (Universitas Batanghari Jambi, 2014)
Indicators of infrastructure, namely the procurement, storage, maintenance and inventory. While performance indicators are the quality, quantity, timeliness, cost-effectiveness, the need for supervision and interpersonal impact. Tebo Traffic Police Office as a government agency responsible for the provision of services to the community in the work area. Servicing the Traffic Police office Tebo guided by an awareness of duties, responsibilities and considerate high perform well so that the police service satisfied. SPSS 20 results obtained equation Y = 0.500 + 0.702 X. From the equation seen the positive effect of infrastructure on the performance of employees in the office of the Traffic Police Tebo evidenced regression coefficients of the equation are owned by 0,702. In other words infrastructure variables can be used as a tool to predict the performance of employees in the Traffic Police office Tebo. The magnitude of the effect seen from the coefficient of determination (r2) of 0.604 or 60.40%. While the remaining 59.60% influenced by other factors, namely discipline, compensation and motivation. Facilities and infrastructure as well as the performance of employees working in the office pretty good Tebo Traffic Police. Based on the statistical test that the regression line is 0.500 + 0.702 X. The coefficient of determination (r2) = 0.59 arau 59%. This means that the effect of infrastructure on the performance of employees in the office Tebo Traffic Police has a very close relationship, and based on the calculation of t = 6.759> t table = 2.0423. It brings a sense hypothesis is accepted.